An Epidural Blood Patch Causing Acute Neurological Dysfunction Necessitating a Decompressive Laminectomy. Issue 1 (March 2015) - Mehta, S.P.; Keogh, B.P.; Lam, A.M.
Abstract : ( Reg Anesth Pain Med . 2014;39(1):78–80)